Protection of Notary Employees In Deed Making Agreements That Are Legally Defective In Terms of Law Number 13 Of 2003 About Employment - Regina Christhalia; Mella Ismelina Farma Rahayu (Journal of Law, Politic and Humanities, 2024)
This research aims to examine how the protection given to notary employees in the event of making deeds that are legally defective is reviewed based on Law Number 13 of 2003 about employment and also regarding the responsibility of notary employees for deeds that are legally defective. This research journal uses a normative juridical research approach. Sourced data from laws and other literature data. The result of the research conducted is that the protection of notary employees has not been specifically regulated in the Notary Profession Law (Undang-Undang Jabatan Notaris), but from what has been described previously, it confirms that labor or worker is very necessary to get protection and has an important role that is needed as well as notary employees who are included as labor and also witnesses in carrying out various tasks are very necessary to get protection so that the welfare and justice for notary employees can be properly guaranteed. Therefore, the author is interested in writing a research with the title Protection of Notary Employees in Legal Defective Deed Making Agreements Reviewed from Law Number 13 of 2003 about employment.